Relationship of AI- Dependency and Reading Comprehension of Pre-Service English Teachers - Basagre, Rey-Mark; Perez, Karen; Argente, Shiela; Assuncion, Marian; Barrion, Rose Anne Marianne; Bersabe , Lerame; Flora, Jerald; Rabino, Jasmin (SEAMEO SEAMOLEC, 2025)
With the increasing integration of Artificial Intelligence (AI) tools in academic settings, this research aims to determine how AI usage influences students' reading comprehension skills. This quantitative study investigates the relationship between reading comprehension and AI dependency among pre-service English Teachers at Central Bicol State University of Agriculture. The study found that first-year students had below-average reading comprehension. In contrast, second-year to fourth-year students demonstrated average comprehension, indicating improvement over time but with room for growth. It revealed moderate AI dependency across all year levels, with third-year students showing the highest reliance on AI for academic purposes. A weak positive correlation between reading comprehension and AI dependency was observed, though not statistically significant, suggesting that AI use alone does not directly affect reading comprehension. The results imply that effective reading comprehension skills does not depend on AI usage, and the importance of critical thinking methods should be emphasized.